Scientific data sharing using clustered-based data sharing in grid environment - Latip, Rohaya; Ibrahim, Hamidah; Al-Hanandeh, Feras Ahmad (Science Publications, 2011)
Problem statement: In a large dynamic network, data can be shared and accessed in an easy manner among researchers from various locations and access provided an efficient protocol to manage the data. Approach: A protocol is needed to ensure the data is consistent and accessible. Results: In this study, we introduced a new protocol, named Clustered-based Data Sharing (CDS) for data sharing in a large dynamic network such as grid computing by using Clustered-based techniques to improve the accessibility. This is due to Clustered-based techniques can ensure that the data is accessible among the members of the grid. To evaluate our model, we developed a simulation model in Java. Conclusion/Recommendations: Our results show that CDS achieves high data accessibility even when the number of nodes or sites is increasing.